What we have learned from the influenza A pH1N1 2009/10 pandemic: high clinical impact of human metapneumovirus and respiratory syncytial virus in hospitalized pediatric patients - Vogel, Markus; Schroten, Horst; Tenenbaum, Tobias (Japanese Journal of Infectious Diseases, 2016)
The influenza pandemic in 2009/2010 shifted public awareness to respiratory tract infections caused by the influenza virus. A prospective study was conducted during the influenza pandemic from November 2009 through April 2010 to determine the causative pathogens and clinical symptoms present in all children and adolescents admitted to the University Children's Hospital, Duesseldorf, Germany, with signs and symptoms of respiratory tract infection. A total of 272 children and adolescents were admitted with symptomes of acute respiratory tract infection (ARI) or influenza-like illness. Viral pathogens were detected in 80% (218/272). However, influenza A pH1N1 infection was only detected in 11% (30/272) of children. Human metapneumovirus (HMPV) and respiratory syncytial virus (RSV) were the predominant identified pathogens that led to the admission of young tachypneic children with pneumonia in the post pandemic phase and the requirement for more intense treatment. During the pandemic and early post-pandemic phase the clinical impact of other respiratory viruses, such as HMPV and RSV, led to a higher clinical disease burden than pH1N1. Consequently, HMPV testing should be performed as routinely as RSV testing in patients hospitalized for ARI. Even while preparing for pandemics, the awareness of other respiratory viruses must be maintained.
Gesehen am 23.01.2019
Advance Publication May 12, 2015